IMPACT OF AMMONIA ON OXIDATIVE METABOLISM IN CERTAIN TISSUES OF ALBINO RAT - J.PRIYADARSHINI; P.NEERAJA (International Journal of Pharma and Bio Sciences, 2015)
Ammonia has received increasing attention over the past few years as a potentially important pollutant. The metabolic changes and potentialities of ammonia in high concentration are reported in all groups of animals as ammonia toxicity and stress. However, at high levels, ammonia is toxic, leading to functional disturbances of the central nervous system that can lead to coma and death. The present study aims to examine the changes in biological oxidative enzymes under sub lethal concentrations of ammonia as a function of chronic stress in Wistar strain albino rat. Lethal doses of ammonium sulphate were determined by the probit method of Finney (1971). Rats were exposed intraperitonially to1/3 of the LD50 dose i.e., 66.5 mg/kg body weight and vitamin-C 40 mg/kg body weight for one month. Liver, kidney and testes were taken for the present study in control, ammonia exposed and ammonia along with vitamin-C treated rats. The selected biological oxidative enzymes are LDH, SDH and MDH, were estimated by using standard methods. The change in these enzyme levels on ammonia stress is discussed.